Validating atlas-guided DOT: A comparison of diffuse optical tomography informed by atlas and subject-specific anatomies - Cooper, Robert J.; Caffini, Matteo; Dubb, Jay; Fang, Qianqian; Custo, Anna; Tsuzuki, Daisuke; Fischl, Bruce; Wells, William; Dan, Ippeita; Boas, David A. (NeuroImage (Orlando, Fla.), 2012)
We describe the validation of an anatomical brain atlas approach to the analysis of diffuse optical tomography (DOT). Using MRI data from 32 subjects, we compare the diffuse optical images of simulated cortical activation reconstructed using a registered atlas with those obtained using a subject's true anatomy. The error in localization of the simulated cortical activations when using a registered atlas is due to a combination of imperfect registration, anatomical differences between atlas and subject anatomies and the localization error associated with diffuse optical image reconstruction. When using a subject-specific MRI, any localization error is due to diffuse optical image reconstruction only. In this study we determine that using a registered anatomical brain atlas results in an average localization error of approximately 18mm in Euclidean space. The corresponding error when the subject's own MRI is employed is 9.1mm. In general, the cost of using atlas-guided DOT in place of subject-specific MRI-guided DOT is a doubling of the localization error. Our results show that despite this increase in error, reasonable anatomical localization is achievable even in cases where the subject-specific anatomy is unavailable.